Characteristics of pore-fracture structure and three-dimensional spatial distribution differences in deep and shallow coal reservoirs: A case study of Junggar Basin - WANG Pengxiang, ZHANG Zhou, YU Wanying, ZOU Qiang, YANG Zhengtao (Youqicang pingjia yu kaifa)
The differences in pore-fracture structures between deep and shallow coal reservoirs significantly affect coalbed methane extraction. Research on these structural differences provides theoretical support for exploring their physical properties and identifying favorable zones for coalbed methane exploration and development. This study analyzed coal samples from deep and shallow coal reservoirs in the Junggar Basin. These samples were tested using scanning electron microscopy, low-temperature N2 adsorption, high-pressure mercury injection, and CT scan. The results showed that, from shallow to deep coal samples, the permeability, total pore volume, and distribution frequency of micropores and macropores gradually decreased. The shallow coal samples exhibited well-developed pores and fractures, with low fractal dimensions in the mesopore and macropore stages, strong homogeneity in pore development, and interconnection between macropores and microfractures. In contrast, the deep coal samples showed relatively isolated pore-fracture development, more complex pore development in the mesopore and macropore stages, and significant mineral filling within pores and fractures. A pore network model for the samples was established using the maximal sphere algorithm to analyze the distribution pattern, morphology, and three-dimensional structural development of the connected pores and fractures. The equivalent pores, throat parameters, and other structural parameters, along with the connectivity, were statistically analyzed. The results revealed that shallow coal samples showed higher connectivity and total porosity compared to the deep samples. The shallow samples exhibited more pores and fractures, with a dominance at the microfracture scale. Additionally, they exhibited shorter throats, larger pore-throat radii, denser pore development, higher coordination numbers, and better connectivity, which facilitated gas flow in the reservoir. The research findings provide experimental data support for the development of deep and shallow coalbed methane in the Junggar Basin using adaptive technologies, and offer valuable guidance for on-site development.